A conceptual approach towards the use of prepositional phrases in Norwegian – the case of ’i’ and ’på’ - Szymańska, Oliwia (Folia Scandinavica Posnaniensia, 2010)
The paper gives an insight into how Polish learners of Norwegian distribute locative prepositions i and på (in and on) in the most basic spatial contexts. The project is set within SLA studies with cognitive theories and conceptual transfer theory as a key-stone. The data which has been analysed is elicited from four main sources. The two most vital ones are based on ASK-corpus (AndreSpråksKorpus) with the total of 800 informants, and a fill-in-the-gaps survey with 90 participants. The overall aim of the project was to discover patterns native speakers of Norwegian use for distributing i and på. Based on this knowledge, I pinpointed potential mistake domains which could motivate conceptual forward transfer for the Polish learners. Thereafter, Polish informants' performance in L2 was analysed with respect to transfer. I propose four potential transfer domains, i.e. different conceptualization of some objects and places, marking abstract and concrete contexts, marking of dynamic situations and lexicon shortages combined with language diversity of Norwegian, which should be taken into consideration when acquiring Norwegian.